Hypomagnesemia in beef cattle from the central region of Argentina: retrospective study - Canton, German Jose; Fernandez, Eduardo Luján; Poo, Juan Ignacio; Spath, Ernesto Juan; Odriozola, Ernesto Raul; Monterubbianesi, María Gloria; Moreno, Fabiana Carina (Centro de Ciências Rurais, Universidade Federal de Santa Maria, 2021)
Hypomagnesaemia (grass tetany) is a metabolic disorder of ruminants due to a reduced dietary intake of magnesium (primary deficiency), incorrect digestibility or associated metabolic factors reducing Mg intake (secondary deficiency). Grass tetany is a production disease responsible for important economic losses in beef herds from Argentina. Several factors influence the development of grass tetany in cattle, including physiological status, weather, soil and forage. This research described a retrospective analysis over the past 20 years, revising the cases of beef cattle clinical hypomagnesaemia registered at the Veterinary Diagnostic Service in INTA Balcarce, Argentina.